Emotional Inteligence in The Qur’an: Study of The Story of The Prophet Musa and Khidr - Ermayani, Tri (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
The concept of emotional intelligence was first proposed by Peter Salovey and John D. Mayer (1990) in their scientific article entitled "Emotional Intelligence." Some time later, the concept of emotional intelligence became widely known after the publication of Daniel Goleman's (1995) work, "Emotional Intelligence: Why It Can Matter More Than IQ." In modern psychological discourse, emotional intelligence is understood as a person's competence in recognizing, interpreting, managing, and using emotions positively and productively. Although Goleman popularized the term emotional intelligence, this concept has actually been embedded in religious narratives long before the emergence of formal psychology. As a guide for the lives of Muslims, the Qur'an presents many stories that illustrate the principles of emotional intelligence through the dynamics of interactions between prophets and ordinary people, facing all their challenges. In QS Al-Kahfi [18]:60-82, especially the story of Prophet Musa and Prophet Khidr, offers a comprehensive case study of the dynamics of emotional intelligence in spiritual, moral, and interpersonal contexts. This study aims to explore how the Qur'an implicitly teaches emotional intelligence through an in-depth analysis of the dialogue, actions, and symbolism in the story.